Developments in high‐speed countercurrent chromatography and its applications in the separation of terpenoids and saponins. Issue 8 (5th April 2016) - Song, Hua; Lin, Jianhong; Zhu, Xuan; Chen, Qing
Abstract : High‐speed countercurrent chromatography is a liquid–liquid separation chromatographic technique, which has the unique feature of eliminating irreversible adsorption using liquid support medium, and is widely used in research and development of traditional Chinese medicine, biochemistry, food, environment analysis, and so on. In this review, some new developments of countercurrent chromatography, for instance cross‐axis countercurrent chromatography, dual countercurrent chromatography, foam countercurrent chromatography, and pH‐zone‐refining countercurrent chromatography are presented. Furthermore, the research and progress in high‐speed countercurrent chromatography techniques and its application in the separation and purification of terpenoids and saponins are reviewed.